Good Agriculture Practices for enhanced farm income and quality of farm produce - Nain, M. S.; Singh, Rashmi (Indian Farming, 2017)
Good Agriculture Practices (GAP) are practices that address environmental, economic and social sustainability for on-farm processes, and result in safe and quality food and non-food agricultural products. The unique grower-to-consumer relationship of farmers markets sets it apart from traditional food retailers.